THE ROLE OF THE UZBEK FAMILY IN SOCIETY AND PERSONAL DEVELOPMENT (Archive of Conferences, 2021)
In the article, comments are made on the role of parents and family in the upbringing of children, stability of socio-psychological environment in the family, the role of national traditions in the upbringing of children, the functions of parents and family in the development of a child as a perfect person.